Targeting CD276 with Adapter-CAR T-cells provides a novel therapeutic strategy in small cell lung cancer and prevents CD276-dependent fratricide - Kristmann, Beate; Werchau, Niels; Suresh, Lakshmi; Pezzuto, Elisabeth L.; Scheuermann, Sophia; Krost, Simon; Schilbach, Karin; Moustafa-Oglou, Moustafa; Mast, Anna-Sophia; Droste, Miriam; Felsberger, André; Kiefer, Lukas; et al. (Journal of hematology & oncology, 2025)
Survival rates in Small Cell Lung Cancer (SCLC) remain dismal, posing a huge medical need for novel therapies. T-cells, engineered to express chimeric antigen receptors (CAR-T) have demonstrated clinical activity against a variety of haematological malignancies. Yet, efficacy against solid tumour entities remains limited.